AN OVERVIEW OF CRITICAL SUCCESS FACTORS FOR IMPLEMENTING 3D PRINTING TECHNOLOGY IN MANUFACTURING FIRMS - Shahrubudin, Nurhalida; Chuan, Lee Te; Ramlan, Rohaizan (Journal of Applied Engineering Science, 2019)
Additive manufacturing, also known as 3D printing or digital fabrication technology, is a process of accumulating deposited layers to form solid 3D objects from 3D models in digital files. 3D printing technology is a fast-emerging technology. Nowadays, 3D printing technology is successfully applied in shaping the globe and producing most of the products used today, from simple plastics to advanced ceramics and metallics. 3D printing technology can print an object layer by layer, by directly depositing the material using computer software, with only just one click. This paper gives an overview of the Critical Success Factors (CSFs) for 3D printing technology in manufacturing firms. The literature found in this paper is mainly from Emerald Insight, Science Direct, Google Scholar and Additive Manufacturing. Briefly. The list of Critical Success Factors can be divided into nine major factors, which are cost, technology, business and support, management and organisation, materials, quality and accuracy, demand, the environment and lastly, research and development.
Keywords: technology; manufacturing; layers; Implementation; digitization; additives